1994
DOI: 10.1007/bf02388435
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in glucose transport in the mouse hippocampus

Abstract: In order to observe glucose transport into the brain, 6-[N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl)amino]-6-deoxyglucose (NBDG), a non-metabolizable and fluorescent glucose analogue, was injected intravenously into mice. After ascertaining that this glucose analogue is non-metabolizable in the brain, the NBDG contents in the blood and brain were measured quantitatively by spectrofluorimetry at 0, 0.5, 2, 5, 10 and 30 min after intravenous injection. The NBDG content in the blood decreased markedly with time, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…6-NBDG, an analogue of 2-NBDG, has been previously used to assess glucose transport in the brain in vivo (Shimada et al, 1994). Because they were concerned that diffusion of 6-NBDG after brain sectioning might blur the fluorescence images, these investigators used a freeze-dry method.…”
Section: Discussionmentioning
confidence: 99%
“…6-NBDG, an analogue of 2-NBDG, has been previously used to assess glucose transport in the brain in vivo (Shimada et al, 1994). Because they were concerned that diffusion of 6-NBDG after brain sectioning might blur the fluorescence images, these investigators used a freeze-dry method.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the non-metabolizable fluorescent glucose analog 6-deoxy- N -(7-nitrobenz-2-oxa-1,3-diazol-4-yl)-aminoglucose (6-NBDG) (Speizer et al ., 1985) combined with high spatial resolution real-time two-photon microscopy, would be effective in addressing this issue in the living brain. Fluorescent glucose analogs have been increasingly used to study glucose transport and metabolism in many cell types as well as in astrocytes and neurons (Shimada et al ., 1994; Porras et al ., 2004; Rouach et al ., 2008). Here we examine the kinetics of 6-NBDG uptake into astrocytes and neurons in the rat barrel cortex, both during resting conditions and sensory stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous work, however, it was found that even if the NBDG was introduced into the mouse blood vessel directly and it was killed 1 min later, no fluorescence was observed in the blood of the brain micro vessels under the low power magnification [9] . This phenomenon seems to result from the quenching of fluorescence by certain blood components.…”
mentioning
confidence: 83%
“…A fluorescent glucose analogue, 6-deoxy-N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl)-amino- In the previous work, we studied glucose transport in brain tissue by using 6-deoxy-N-(7-nitrobenz-2-oxa-1, 3-diazol-4-yl)-aminoglucose (NBDG) and confocal laser scanning microscope (CLSM) [9] . The fluorescent labeling compound, NBDG, has an excitation and emission maximum of 480 nm and 550 nm, respectively.…”
mentioning
confidence: 99%